Students Language Attitude During Distance Learning at SMP Angkasa Kuta - Bali - Putri, I Gusti Ayu Vina Widiadnya (International Journal for Educational and Vocational Studies, 2020)
This study investigated the students attitude during distance learning at SMP Angkasa Kuta - Bali. The impact of the corona virus outbreak (Covid-19) has also been felt by the education sector. Studying at home is a good way to break the spread of the corona virus. Distance learning is carried out with the supervision of a teacher and parents. This is what distinguishes distance learning from independent learning. In distance learning activity, one of the way to communicate each other is by sending text message. Most of the students are not accustomed to use written language well in formal communication. This activities requires them to text the message word by word to their teachers. Studying attitude in language helps all stakeholders in various ways. This can investigate effective student attitudes with the teacher using good language. In addition students can be confident, learn politeness in language with different learning styles. Students have their own language attitude in communication. In addition, they also have diverse views about the learning process. The data sources chosen in this study were the students of SMP Angkasa, Kuta-Bali. The analysis is done by descriptively method. To make the analysis clearer, all of data were completed with explanation and supported by the cart to show percentage of the data. The theory from Richard, Platt, & Platt (1992) about Language Attitude used to analyze the various kinds of language attitudes. This study used questioner to get some reason of the language used by the students as well.  This study found that there are two classifications of language attitudes used by students in communication using written language. Both Language Attitudes of students in terms of their Behavioral and Language attitude in term of their emotional are found. Based on this classification, student prefer use negative language attitude in their respond to the teacher. The reason why some students prefer use negative language attitude in their respond to the teacher have been found by the result of questioner.